A High‐Mobility Hole Bilayer in a Germanium Double Quantum Well. Issue 5 (25th March 2022) - Tosato, Alberto; Ferrari, Beatrice; Sammak, Amir; Hamilton, Alexander R.; Veldhorst, Menno; Virgilio, Michele; Scappucci, Giordano
Abstract: A hole bilayer in a strained germanium double quantum well is designed, fabricated, and studied. Magnetotransport characterization of double quantum well field‐effect transistors as a function of gate voltage reveals the population of two hole channels with a high combined mobility of 3.34 × 10 5 cm 2 V − 1 s − 1 $3.34× 10^{5}\ {{\rm cm}^2\nobreakspace {\rm V}^{-1}\nobreakspace {\rm s}^{-1}}$ and a low percolation density of 2.38 × 10 10 cm − 2 $2.38 × 10^{10}\ {{\rm cm}^{-2}}$ . The individual population of the channels from the interference patterns of the Landau fan diagram was resolved. At a density of 2.0 × 10 11 cm − 2 $2.0× 10^{11}\ {{\rm cm}^{-2}}$ the system is in resonance and an anti‐crossing of the first two bilayer subbands is observed and a symmetric‐antisymmetric gap of ≈ 0.69 meV $≈ {0.69}\ {\rm meV}$ is estimated, in agreement with Schrödinger‐Poisson simulations. Abstract : A high‐mobility hole bilayer is demonstrated in strained germanium double quantum wells. These results open up new exciting possibilities for the germanium quantum information route, from quantum devices and circuits with increased connectivity to the study of excitons in the quantum Hall regime.